Very Large Eddy Simulation of Lean Premixed Flames to Imposed Inlet Velocity Oscillations. Issue 14 (26th October 2022) - Huang, Ziwei; Guo, Tao; Han, Xingsi; Mao, Junkui
ABSTRACT: The present work describes an assessment and validation of the newly developed Very-Large Eddy Simulation (VLES) method for the numerical study of complex non-linear response of a lean premixed flame to acoustic velocity fluctuations. The VLES method is a self-adaptive turbulence method which can achieve seamless switching between RANS, LES, and finally approaching DNS. It is extended to the turbulent combustion simulation in the present study. The selected test case is a bluff-body stabilized lean premixed turbulent flame with acoustic forcing. Turbulence modeling is achieved using the VLES method and the premixed turbulent combustion is modeled using the Thickened Flame Model (TFM) combining a reduced two-step chemical reaction mechanism. Harmonically varying velocity fluctuation is imposed on the inlet to introduce the acoustic forcing. Three types of flow including the cold flow, unforced reactive flow, and forced reactive flow are used to validate the simulation method. The mean velocity, dynamic response of the flame to inlet velocity forcing and the quantitative response of the heat release rate are captured by the present calculations with very reasonable accuracy compared with the experimental data. The present VLES predictions are comparable or even better than the present LES results using the combustion model and the same computational grid. This work thus confirms that the VLES methodology is capable of successfully predicting the response of lean premixed turbulent flame to acoustic forcing.